ASAS ITIKAD BAIK DALAM PERJANJIAN SEWA MENYEWA RUANGAN PERKANTORAN ANTARA PENYEWA DENGAN PEMILIK GEDUNG PT. SURYA DUMAI INDUSTRI TBK DI KOTA PEKANBARU - Hutabarat, Tio Dara Sabri; Firdaus, Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The rental agreement for the Surya Dumai building space between PT. Surya Dumai Industri Tbk with tenants regarding the rights and obligations of tenants and owners are regulated in chapter II regarding the Lease Agreement. In chapter IV concerning Leases which states that: